THEORETICAL AND METHODOLOGICAL APPROACHES TO IT INFRASTRUCTURE MANAGEMENT IN CONDITIONS OF DIGITALIZATION - KUSTOV, Vitaliy; KOVALENKO, Marina (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article proves that the formation and support of IT infrastructure developing is a key strategic factor in the effective functioning of enterprises and organizations. There are the interpretations of the concepts ‘IT infrastructure’, ‘information infrastructure’, ‘technological infrastructure’ and ‘supporting infrastructure’. It has been found that the IT infrastructure needs constant support and updating to ensure the safety and reliability of data, devices, IT services, tools, technological processes, information, and communication technologies. The components of the organization's IT infrastructure that meet the needs and business development plan are given. It has been established that IT infrastructure components can be deployed, organized and implemented in various ways. The main tasks of the IT infrastructure and its purpose are also given. The article provides the information that the modern version of the organization's IT infrastructure is cloud infrastructure, which is quite effective for small and medium-sized businesses with a limited budget. It was found out the virtualization of the IT infrastructure of the enterprise is provided by the virtualization of servers, applications, workstations, the use of cloud computing, optimization of the information network, interaction on demand. The areas of management that have developed from the need to maximize the value created by IT assets are characterized: ITOM, ITSM and ITAM. Important to know the role of the IT infrastructure management system because it is manifested in the proactive administration and management of technological tools, in particular: monitoring of errors and problems; patch tracking; tracing all errors back to their original sources. Moreover, it has been established that the role of IT infrastructure security is becoming more complicated as business entities move to cloud models, hybrid models, multi-cloud technologies, etc. Finally, the model of providing cloud services, with the help of which IT organizations can purchase virtualized computing resources from a third-party provider and access them via the Internet, is called infrastructure services (IaaS).
Keywords: hardware; business processes; information; IT infrastructure'; software; management; digitization